Assessment of good practices in blended learning as an institutional approach for enhancing students’ learning experiences in higher institution (2015)
Methods used for teaching and learning have been found to directly affect and substantially enhance students' learning experiences but the extent to how good practices in blended learning has enhanced student learning experiences in higher institutions has not been sufficiently examined. This study assesses good practices in blended learning as an institutional approach for enhancing students learning experiences in higher institution. Mixed method was adopted for the study (qualitative and quantitative approach) qualitative approach made use of structural interview conducted on twenty coordinators and lecturers while the structured questionnaire titled “Good Practices in Blended Learning Questionnaire ” constructed by the researcher was pilot tested that yielded Cronbach Alpha reliability of r=. 79 was used for data collection. Simple random sampling technique was used to select 250 University of Ibadan Distance Learning students. Data collected from interview was analyzed using thematic approach while quantitative data was analyzed using independent t-test. The result shows a significant mean difference between face to face (M-9.87, S.D. =1.96) and on-line interaction (M = 5.40, S.D-1.91) in cooperation among student (t=2.334, p<0:05). Also, a significant mean difference exist between on-line (M= 7.95, S.D=1.96) and face to face interaction (M=13.30, S.D. =1.66) in course satisfaction among the students (t= 17.87, p<.05). Individual differences does not significantly influence student's learning in both on-line (M=8.50, S.D. = 67) and traditional face to face (M=8.31, S.D. =1.22) interaction (t = 1.87, p<.05). Thematic analysis revealed that range of learning resources; lectures, power point presentation among others were provided to support online quizzes, and class exercise. Hence, blended learning environment is judiciously implemented and hold promise for students learning achievement.